Altitudinal effects on life history parameters in populations of Liolaemus pictus argentinus (Sauria: Liolaemidae) - Gutiérrez, Joel Antú (2013)
We used skeletochronology to assess the age structure, body size and sexual maturity in two populations of Liolaemus pictus argentinus from San Carlos de Bariloche, Argentina. The species occupies a wide Altitudinal range within the Patagonian Lake District which enabled us to choose populations from two climatic extremes: 771 m a.s.l. and 1615-1769 m a.s.l. Age of sexual maturity in both populations of L. p. argentinus is achieved with a minimum body size of 49 mm. However, at the high-altitude site, lizards matured between the ages of three to six years and had a lifespan of eight years limiting some individual?s reproductive life to only two years. Lizards from the low-altitude site achieved maturity at the age of four and lived until the age of nine years old. Despite the environmental variations between sites populations? growth curves? patterns were similar represented by a rapid initial growth rate of 10.3 mm/year in youngest juvenile which slowed considerably to 4.9 mm/year after attaining sexual maturity, as energy is reallocated towards reproduction, to finally grow at a rate of 0.1 mm/year in the oldest adults. Present results show intraspecific differences in L. pictus, whether it results from adaptive polymorphism or physiological plasticity remains uncertain.